District newspapers as a chronicler of the Arkhangelsk North history - Mikhail V. BUTORIN (Northern Arctic Federal University, 2019)
The article discusses the creation and operation of district periodicals in the Arkhangelsk Oblast. The author analyzed their role in solving problems in different periods and evaluated the place of the “district” in the relations of the state and local authorities. Based on a study of modern local periodicals, the author concluded that the press, freed from the CPSU dictates, became dependent on new power and was forced to cover mainly its activities and achievements. The way out of this situation is the creation of mu-nicipal newspapers.